New records of plants eaten by the tapir, Tapirus bairdii (Perissodactyla: Tapiridae) in Braulio Carrillo National Park, Costa Rica (UNED Research Journal, 2020)
We report Tapirus bairdii eating Schefflera rodriguesiana and Gunnera insignis in Volcán Barva, Costa Rica.
Keywords: Tapirus bairdii; tapir; herbivory; Barva Volcano; Schefflera rodriguesiana; Gunnera insignis